2020
DOI: 10.1039/d0nj00837k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative ability of organic iodine(iii) reagents: a theoretical assessment

Abstract: Computational prediction of the oxidative ability of hypervalent iodine reagents was performed based on redox potentials, calculated at the B3LYP/6-311+G(d,p) level of theory with the SDD ECP46MDF pseudopotential for the iodine atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Diacetoxyiodobenzene (PhI(OAc) 2 ) and related species are versatile I(III) oxidants with applications in organic and inorganic chemistry [1] . Replacement of the acetate ligands with more electron poor fragments results in derivatives that are stronger oxidants [2] . One such derivative with an increased oxidative capacity is PhI(OTf) 2 which has had reported use as an in situ generated species in solution by several groups, including our own.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diacetoxyiodobenzene (PhI(OAc) 2 ) and related species are versatile I(III) oxidants with applications in organic and inorganic chemistry [1] . Replacement of the acetate ligands with more electron poor fragments results in derivatives that are stronger oxidants [2] . One such derivative with an increased oxidative capacity is PhI(OTf) 2 which has had reported use as an in situ generated species in solution by several groups, including our own.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Replacemento ft he acetate ligands with more electron poor fragments results in derivatives that are stronger oxidants. [2] One such derivative with an increasedo xidative capacity is PhI(OTf) 2 which has had reported use as an in situ generateds pecies in solution by severalg roups, including our own. In organic chemistry PhI(OTf) 2 has purported use in formation of hydrazones, [3] oxyaminations, [4] dizaeniums, [5] synthesis of functionalized cyclopropane rings, [6] cyclization of hydroxystilbenes or carboxylic acids, [7] functionalization of acetylenes, [8] aryl CÀHa lkylations, [9] and alpha arylations.…”
mentioning
confidence: 98%
“…However, despite the practical significance of HIRs, redox potentials of them has not been sufficiently evaluated until now, only limited of redox potential values of HIRs were reported in literatures ( Figure 2 ) (Charpentier et al, 2015 ; Roth et al, 2016 ; Vaillant and Waser, 2017 ). Just in 2020, Radzhabov and coworkers reported new calculated values of the relative redox potentials of [bis(acetoxy)iodo]-arenes (Radzhabov et al, 2020 ). The influence of various substituents and the effects of various solvents on the reduction potentials of HIRs was both detailed evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts in our lab to synthesize diacetate compounds 12DMAP and 12IM have been unsuccessful as combination of 5DMAP and PhI(OAc)2 resulted in no reaction, likely due to the relatively modest oxidative ability of PhI(OAc)2. 26 Recently we reported that the cationic difluorogold systems (6DMAP, 6IM) can undergo metathesis reactions with [PhI(pyridine)2] 2+ species via nucleophilic attack from fluoride onto the iodine resulting in transfer of pyridine to the gold and generation of PhIF2. 27 To investigate if 6DMAP can also react with I(III) species bearing anionic ligands to give 12DMAP, which we were unable to synthesize oxidatively from Au(I), it was reacted with PhI(OAc)2 in CH3CN, resulting in a colour change from yellow to orange.…”
Section: Reaction Of Au(iii) Difluorides With Phi(oac)2mentioning
confidence: 99%